If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x = 7y + -15 Reorder the terms: 3x = -15 + 7y Solving 3x = -15 + 7y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '3'. x = -5 + 2.333333333y Simplifying x = -5 + 2.333333333y
| -2g=-3g+6 | | -8m=-10m+10 | | 6p+10=7p | | -21/7x=20/21 | | 2sin(x-30)=1 | | -10x-4=-6 | | 2(x+7)+23=9-3(x-1) | | -10+9d=8 | | 7x-13=10x+8 | | x^2*36=y^2 | | 0.5*x^3-0.5*x-3=0 | | sin(2t)=-0.56 | | 4x+y=-27 | | 4sen^2(x)-8sen(x)-5=0 | | y+8=0.1(x-3) | | 172n=184 | | y-1=0.2(x+3) | | y+4=10(x-3) | | 361n=130 | | 4-(2x-11)= | | 130n=361 | | 575n=980 | | 361n=172 | | 2(v-3)=9v+36 | | 8u+32+3u=-23 | | 2x=5(2-4x) | | 1/sinh(x) | | ln(x^2-25)=10+ln(75) | | X^5/15×X^7/15 | | 3(a+2)+2(4+b)= | | (k-1)x^2-2kx+k^2=0 | | -2v+8(v-3)=-6 |